2020
DOI: 10.1177/0743915619889052
|View full text |Cite
|
Sign up to set email alerts
|

Look, Puppies! A Visual Content Analysis of Required Risk Statements Embedded in Direct-to-Consumer Pharmaceutical Advertising

Abstract: Direct-to-consumer advertising (DTCA) on television is a prominent source of information about medical conditions and their potential treatments. In the United States, the Food and Drug Administration (FDA) requires that DTCA include a major statement presenting the medication’s most important risk information in a fair and balanced manner. However, there is growing concern about the visual content that accompanies this risk information within DTCA major statements. Specifically, the FDA has failed to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Figure 1 indicates a divergence between the visual-only condition and other two conditions in risk perceptions following the initiation of the major statement, and a relative convergence of all three groups at its conclusion. This finding is consistent with previous research (Avery, Eisenberg, and Simon 2012; Kaphingst et al 2004; King, Koppenhafer, and Madrigal 2021; Macias, Pashupati, and Lewis 2007) indicating that visual content delivered during the major statement is incongruent with auditory content.…”
Section: Studysupporting
confidence: 93%
See 3 more Smart Citations
“…Figure 1 indicates a divergence between the visual-only condition and other two conditions in risk perceptions following the initiation of the major statement, and a relative convergence of all three groups at its conclusion. This finding is consistent with previous research (Avery, Eisenberg, and Simon 2012; Kaphingst et al 2004; King, Koppenhafer, and Madrigal 2021; Macias, Pashupati, and Lewis 2007) indicating that visual content delivered during the major statement is incongruent with auditory content.…”
Section: Studysupporting
confidence: 93%
“…For example, Kaphingst et al (2004) found that 91% of the DTCA included in their study featured positive or neutral visual imagery during the major risk statement (see also Avery, Eisenberg, and Simon 2012). Using a larger set of advertisements, King, Koppenhafer, and Madrigal (2021) recently reported that DTCA major statements feature significantly more positive imagery, complex imagery, and on-screen motion than non–major statement portions of the same ad.…”
Section: Theoretical Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Although deception may include instances in which a seller is taken advantage of by a buyer, our focus is on situations where the seller profits at the expense of the buyer. Duping examples are varied and include instances in which buyers fall prey to advertising created to mislead (Darke and Ritchie, 2007;Hastak and Mazis, 2011) or distract (King et al, 2021). Other contexts include the victimization of buyers by sellers of counterfeit goods (Mavlanova et al, 2008) and the use of online appeals disguised to fool consumers (Campbell and Grimm, 2019).…”
Section: Introductionmentioning
confidence: 99%